Day 3 Wed, May 04, 2016 2016
DOI: 10.4043/27142-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Studies of Microbiologically Influenced Corrosion of Mooring Chains

Abstract: Severe corrosion found on steel mooring components (CSMC) at several sites worldwide has caused concern in recent years as to whether the components can safely meet their design life. A pilot study was initiated to understand the underlying corrosion causes with the aim of developing successful CSMC mitigation methods. In 2014, a field test was conducted offshore at two different locations in West Africa in order to confirm the contribution of microbiologically influenced corrosion (MIC) to CSMC. The study pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Gulf of Guinea samples showed <0.005% zetaproteobacteria OTUs, suggesting that, at this particular site, ALWC was not a major concern. The low levels of nitrate in the water (Witt et al, 2016) provided further evidence for this suggestion. Recent work has indicated that steel structures positioned on the sediment layer may be more likely to develop biofilms containing iron-oxidizing bacteria (McBeth and Emerson, 2016).…”
Section: Biofilmsmentioning
confidence: 75%
See 2 more Smart Citations
“…The Gulf of Guinea samples showed <0.005% zetaproteobacteria OTUs, suggesting that, at this particular site, ALWC was not a major concern. The low levels of nitrate in the water (Witt et al, 2016) provided further evidence for this suggestion. Recent work has indicated that steel structures positioned on the sediment layer may be more likely to develop biofilms containing iron-oxidizing bacteria (McBeth and Emerson, 2016).…”
Section: Biofilmsmentioning
confidence: 75%
“…In November 2014, coupons were exposed in the upper water column, 3 m below the surface of the sea, 113 km off the coast in the Gulf of Guinea. The pH of the water at sampling was 6.94, it contained <0.001 mg l À1 phosphate and total nitrate, 2960.3 mg l À1 sulfate and 28.45 mg l À1 ammonium ions (Witt et al, 2016). The system was originally designed to withstand exposure in the field for four to eight weeks (28e56 days).…”
Section: Metal Coupons and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…This is due to their significant impact on the corrosion of marine structures, such as pipelines, ships, and oil rigs, which can result in economic losses and environmental hazards [ 50 ]. Methanogens and sulfur oxidizers are the primary archaeal groups involved in marine microbial corrosion, as studies have shown [ 18 , 51 , 52 , 53 , 54 ]. Methanogens produce methane by reducing carbon dioxide or organic matter in anoxic sediments or water [ 55 ].…”
Section: Microorganisms Involved In Marine Micmentioning
confidence: 99%
“…Near 40% of incidences of biocorrosion in oil reservoir souring, pipelines and fitting, wire ropes for mooring applications have been reported related to microbiologically influenced corrosion (MIC) [1,2]. This form of electrochemical corrosion in the form of crevices or localized pits were observed in many environments facilitated or accelerated by the presence of micro-organisms [3].…”
Section: Introductionmentioning
confidence: 99%